Peranan Teknologi Komunikasi dalam Menciptakan Masyarakat Informasi di Indonesia - Dwi Ratna A; Vienda A; Florencius S; Santi S (FISIP Universitas Atma Jaya Yogyakarta, 2004)
Information society concept has often been heard and analyzed following with information and communication technology development which can’t be avoided by society. At the beginning, information society comes up from the awareness how important information current is. Nations compete for preparing many tools to realize a transition to aim the dream of information society. Computerization as a requirement to concrete information society is claimed to faster the society existence including e-government effort. However, technology can not only be implemented without considering some aspects because it can make new problems.